Duo of (–)-epigallocatechin-3-gallate and doxorubicin loaded by polydopamine coating ZIF-8 in the regulation of autophagy for chemo-photothermal synergistic therapy. (9th January 2020) - Chen, Xuerui; Tong, Rongliang; Liu, Bingbing; Liu, Hua; Feng, Xiaode; Ding, Shiping; Lei, Qunfang; Tang, Guping; Wu, Jian; Fang, Wenjun
Abstract : A pH- and photothermal-responsive zeolitic imidazolate framework (ZIF-8) compound was designed for loading a dual-drug in the tumor site and improving their curative effects. Abstract : To achieve highly systemic therapeutic efficacy, chemotherapy is combined with photothermal therapy for chemo-photothermal synergistic therapy; however, this strategy suffers from high toxicity and unsatisfactory sensitivity for cancer cells. Herein, we developed a pH- and photothermal-responsive zeolitic imidazolate framework (ZIF-8) compound for loading a dual-drug in the tumor site and improving their curative effects. Since autophagy always accompanies tumor progression and metastasis, there is an unmet need for an anticancer treatment related to the regulation of autophagy. Green tea polyphenols, namely, (–)-epigallocatechin-3-gallate (EGCG) and doxorubicin (DOX), both of which exhibit anticancer activity, were dual-loaded via polydopamine (PDA) coating ZIF-8 (EGCG@ZIF-PDA-PEG-DOX, EZPPD for short) through hierarchical self-assembly. PDA could transfer photothermal energy to increase the temperature under near-infrared (NIR) laser irradiation. Due to its pH-response, EZPPD released EGCG and DOX in the tumor microenvironment, wherein the temperature increased with the help of PDA and NIR laser irradiation. The duo of DOX and EGCG induced autophagic flux and accelerated the formation of autophagosomes. In a mouse HeLa tumor model, photothermal-chemotherapy could ablate the tumor with a significant synergistic effect and potentiate the anticancer efficacy. Thus, the results indicate that EZPPD renders the key traits of a clinically promising candidate to address the challenges associated with synergistic chemotherapy and photothermal utilization in antitumor therapy.